Effectiveness And Composition Of Anco Net (Lift Net) In Bungko Lor Waters, Cirebon District, West Java - Andini Putri, Didha; Susilawati, Evi; Jatnika, Danu (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
Cirebon Regency is topographically located at an altitude of 0-130 km above sea level and is located along the north coast of Java. Geographically and demographically, Cirebon Regency is very suitable for the development of capture fisheries potential, seen from the livelihoods of the population who work as fishermen. The potential of fishery resources in cirebon district revealed a situation is very possible to be developed in order to economic development in cirebon.The net anco ( elevator net ) is one of kinds of tools catch the fish environment friendly. very simpleOne of those potential fishing in bungko lor need to further review, relating to the operation of an instrument. The community fishermen bungko lor cirebon district is still hampered on increased productivity in an effort do police operations. The purpose of this study is to find the effectiveness and composition of the fish anco (elevator net) that is operated on day and night of the results of the water at around 6 catch bungko lor .A method of descriptive of the receipt of the data is survey and direct observation in the field as well as in data collection by staying tightly focused in a case .The sampling method of collected data based on fishermen time operating in waters bungko lor later in analysis using chi-square t test and test it. Catch the elevator anco ( net ) during research consisting of 4 types of shrimp jerbung ( penaeus merguiensis deman ), shrimp windu ( penaeus monodon ), fish mullet ( moolgarda seheli ), and bloso ( glossogobius giuris ).Shrimp jerbung catch is the most during the research 37,1 kg of ( 82 % ), shrimp windu 4,8 kg of ( 9 % ), fish mullet 3,9 kg of 7 % and fish bloso 0,9 kg of 2 %.